Effective treatment with combination of peripheral 5‐hydroxytryptamine synthetic inhibitor and 5‐hydroxytryptamine 2 receptor antagonist on glucocorticoid‐induced whole‐body insulin resistance with hyperglycemia. Issue 6 (5th May 2016) - Ma, Shaoxin; Li, Tao; Guo, Keke; Li, Xin; An, Shanshan; Hou, Shanshan; Chen, Ru; Yang, Bo; Liu, Siyu; Fu, Jihua
Abstract: Aims/Introduction: Our previous study found that dexamethasone‐induced insulin resistance (IR) was involved in 5‐hydroxytryptamine (5‐HT) synthesis and 5‐hydroxytryptamine 2 receptor (5‐HT2 R) in the periphery. The present study examined the effects of inhibitions of both peripheral 5‐HT synthesis and 5‐HT2 R on dexamethasone‐induced IR. Materials and Methods: Male rats were exposed to dexamethasone for 10 days, then treated with or without a 5‐HT2 R antagonist, sarpogrelate, a 5‐HT synthetic inhibitor, carbidopa, alone or in combination for 20 days. Results: Dexamethasone‐induced whole‐body IR, with glucose intolerance, decreased insulin sensitivity, hyperglycemia, hyperinsulinemia and dyslipidemia, could be effectively abolished by sarpogrelate or/and carbidopa, whereas IR‐related actions of dexamethasone in tissues were accompanied by increased 5‐HT synthesis in the liver and visceral adipose, and upregulated 5‐HT2 R (5‐HT2 A R and 5‐HT2 B R) expression in these two tissues as well as in skeletal muscle. Sarpogrelate or/and carbidopa treatment significantly abolished dexamethasone‐caused tissue‐specific IR. In the liver, increased gluconeogenesis, triglycerides and very low‐density lipoprotein syntheses with steatosis, and downregulated expression of plasmalemmal glucose transporter‐2 were markedly reversed. In the visceral adipose and skeletal muscle, downregulated expression of plasmalemmal glucose transporter‐4 was significantly reversed, and increased lipolysis was also reversed in the visceral adipose. Dexamethasone‐induced activations of hepatic mammalian target of rapamycin serine 2448, and S6K threonine 389/412 phosphorylation were also abolished markedly by sarpogrelate or/and carbidopa. Co‐treatment with sarpogrelate and carbidopa showed a synergistic effect on suppressing dexamethasone actions. Conclusion: Inhibitions of both peripheral 5‐HT synthesis and 5‐HT2 R are expected to be a dependable target for treatment of steroid‐induced diabetes. Abstract : Dexamethasone‐induced whole‐body IR, marking with glucose intolerance, decreased insulin sensitivity, hyperglycemia, hyperinsulinemia and dyslipidemia, could be effectively abolished by sarpogrelate or/and carbidopa, while IR‐related actions of dexamethasone in tissues were accompanied by increased 5‐HT synthesis in the liver and visceral adipose, and up‐regulated 5‐HT2R (5‐HT2AR and 5‐HT2BR) expression in both tissues as well as skeletal muscle.